Strategi Pengembangan Wisata Pantai Biru dalam Upaya Menarik Kunjungan Wisatawan (Studi Kasus Desa Telaga Biru Kecamatan Tanjung Bumi Kabupaten Bangkalan) - Asiya Febrianti; Akhmad Sirojudin Munir; Sutopo Sutopo (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
Indonesia has a lot of potential tourist objects scattered throughout the region that can be relied on to become a tourist attraction that is able to attract local and foreign tourists. Bangkalan Regency has a very potential area in the tourism sector because it has many interesting tourist objects. Telaga Biru village has a very interesting tour, pristine nature, a calm and comfortable atmosphere, namely blue beach tourism. Blue beach tourism is always developing to increase tourist visits. Indicators of the success of a tourist attraction can be measured by the number of tourist visits. This research is a qualitative research, while the type of research used is a qualitative research with a descriptive approach. Data collection was carried out through research instruments in the form of interviews, observations, and documentation. Then check its validity using the triangulation technique. The results of this study are: 1. tourism development strategies in an effort to attract tourist visits, in developing tourism by adding tourist attractions such as photo spots, swimming pools, water bikes, plastic flower trees, flower tunnels, and fish therapy, air bicycles, and air balloon. The promotions used are through social media, Facebook, Instagram, YouTube, and websites. 2. Factors that support the development of blue beach tourism, namely, natural resources, good security, a comfortable atmosphere, the role of social media, a supportive community. While the inhibiting factors for the development strategy are, internal factors have not been well organized with tourism potential as well as facilities and infrastructure, while external factors are the lack of road access for bus vehicles because this tour is located in community settlements, and also there is no budget from the government.